Odpowiedzi

Najlepsza Odpowiedź!
2010-03-15T16:06:36+01:00
A)x+1=-3(x+5)
x+1=-3x+(-15)
x+3x=-15-1
4x=-16 I:4
x=-4
b)2(x-1)-3(x-2)=6
2x-2-3x-6=6
2x-3x=6+2+6
-x=14 I*(-1)
x=-14
c)2(x+3)+3(x-6)=18
2x+6+3x-18=18
2x+3x=18-6+18
5x=30 I:5
x=6
d)(3x-5):5=(2x-7):4
3/5x-1=1/2x-7/4
3/5x-1/2x=7/4+1
6/10x-5/10x=11/4
1/10x=11/4 I*10
x=55/2
x=27 1/2
e)(3x-4):2=(4x-5):3
3/2x-2=4/3x-5/3
3/2x-4/3x=-5/3+2
9/6x-8/6x=1/3
1/6x=1/3 I*6
x=2
f)(x-5):4=(x+3):2
1/4x-5/4=1/2x+3/2
1/4x-1/2x=3/2+5/4
1/4x-2/4x=6/4+5/4
-1/4x=11/4 I*(-4)
x=-11